The Growing Burden of Adolescent Thyroid Dysfunction: Pathophysiology and Homeopathic Strategies (Homoeopathy for All, 2026)
Thyroid dysfunction, traditionally regarded as an adult-onset condition, is increasingly being recognized in adolescent populations worldwide. Thyroid hormones play a fundamental role in growth, pubertal maturation, neurocognitive development, and metabolic regulation, making adolescence a particularly vulnerable period for thyroid dysfunction., Even mild deficiencies in thyroid hormone availability can influence linear growth, bone mineralization, lipid metabolism, menstrual regularity, and psychological wellbeing during this critical developmental window. Early recognition is therefore essential, as untreated hypothyroidism in adolescence may have long-term implications for physical and cognitive outcomes.
Keywords: Thyroid; dysfunction; traditionally; increasingly